The role of circadian rhythm regulator PERs in oxidative stress, immunity, and cancer development - Baimei Zhao; Eugenie Nepovimova; Qinghua Wu (Cell Communication and Signaling)
Abstract The complex interaction between circadian rhythms and physiological functions is essential for maintaining human health. At the heart of this interaction lies the PERIOD proteins (PERs), pivotal to the circadian clock, influencing the timing of physiological and behavioral processes and impacting oxidative stress, immune functionality, and tumorigenesis. PER1 orchestrates the cooperation of the enzyme GPX1, modulating mitochondrial dynamics in sync with daily rhythms and oxidative stress, thus regulating the mechanisms managing energy substrates. PERs in innate immune cells modulate the temporal patterns of NF-κB and TNF-α activities, as well as the response to LPS-induced toxic shock, initiating inflammatory responses that escalate into chronic inflammatory conditions. Crucially, PERs modulate cancer cell behaviors including proliferation, apoptosis, and migration by influencing the levels of cell cycle proteins and stimulating the expression of oncogenes c-Myc and MDM2. PER2/3, as antagonists in cancer stem cell biology, play important roles in differentiating cancer stem cells and in maintaining their stemness. Importantly, the expression of Pers serve as a significant factor for early cancer diagnosis and prognosis. This review delves into the link between circadian rhythm regulator PERs, disruptions in circadian rhythm, and oncogenesis. We examine the evidence that highlights how dysfunctions in PERs activities initiate cancer development, aid tumor growth, and modify cancer cell metabolism through pathways involved in oxidative stress and immune system. Comprehending these connections opens new pathways for the development of circadian rhythm-based therapeutic strategies, with the aims of boosting immune responses and enhancing cancer treatments.